上顎癌の画像診断 - 村上, 秀明; 辻本, 友美; 島本, 博彰; 笹井, 正思 (日本口腔外科学会雑誌, 2017)
Maxillary carcinoma is a common cancer in the oral cavity. The gingiva is the second frequent site following the tongue in the oral cancers. At the first visit, patients often complain a pain and swelling at a primary site.　Histopathologically the squamous cell carcinoma is most dominant, and the adenoid cystic carcinoma is the second in the maxillary carcinoma.　Although the primary site of the maxillary carcinoma can be easily seen and palpated, the tumor invasion to inner part is not seen. So, the diagnostic imaging plays an important role. It is difficult to diagnose metastases to regional neck lymph nodes and distant organs without the diagnostic imaging, which is important for planning the scope of resection and further treatment and for differentiating between normal and metastatic lymph nodes as well as between a recurrence and scars or complications after surgery or radiation therapy.　Diagnostic imaging is performed as part of the routine work-up in the maxillary carcinoma. However, it is difficult to interpret the results at the early stages of the disease.　The following imaging modalities are used in a diagnosis of the maxillary carcinoma; panoramic radiographs, computed tomography(CT), magnetic resonance imaging, PET or PET/CT and ultrasound.　The objective of this article is to describe the maxillary carcinoma as it appears in different imaging methods considering both their advantages and limitations.